Perchlorate and chlorate reduction by the Crenarchaeon Aeropyrum pernix and two thermophilic Firmicutes. Issue 6 (23rd October 2015) - Liebensteiner, Martin G.; Pinkse, Martijn W.H.; Nijsse, Bart; Verhaert, Peter D.E.M.; Tsesmetzis, Nicolas; Stams, Alfons J.M.; Lomans, Bart P.
Summary: This study reports the ability of one hyperthermophilic and two thermophilic microorganisms to grow anaerobically by the reduction of chlorate and perchlorate. Physiological, genomic and proteome analyses suggest that the Crenarchaeon A eropyrum pernix reduces perchlorate with a periplasmic enzyme related to nitrate reductases, but that it lacks a functional chlorite‐disproportionating enzyme (Cld) to complete the pathway. A eropyrum pernix, previously described as a strictly aerobic microorganism, seems to rely on the chemical reactivity of reduced sulfur compounds with chlorite, a mechanism previously reported for perchlorate‐reducing A rchaeoglobus fulgidus . The chemical oxidation of thiosulfate (in excessive amounts present in the medium) and the reduction of chlorite result in the release of sulfate and chloride, which are the products of a biotic–abiotic perchlorate reduction pathway in Ae . pernix . The apparent absence of Cld in two other perchlorate‐reducing microorganisms, C arboxydothermus hydrogenoformans and Moorella glycerini strain NMP, and their dependence on sulfide for perchlorate reduction is consistent with the observations made on A r. fulgidus . Our findings suggest that microbial perchlorate reduction at high temperature differs notably from the physiology of perchlorate‐ and chlorate‐reducing mesophiles and that it is characterized by the lack of a chlorite dismutase and is enabled by a combination of biotic and abiotic reactions.